A Cross-sectional Study to Understand the Reasons for Failure to Vaccinate Eligible Children with Measles-containing Vaccine among the Clinically Diagnosed Measles Cases during the Outbreak (2022) in a District of Maharashtra - Sudhir V Sane; Jayashree R Balip; Satish S Mali (Pediatric Infectious Disease)
The measles outbreak occurred in many parts of India, including Maharashtra, in the second half of 2022. We noticed that almost all of these patients were either completely unvaccinated or partially vaccinated for measles. This study was initiated to study reasons for inadequate vaccination in these children. Materials and methods: Patients suffering from measles who had missed vaccination for a period of at least 1 month were included. The caretakers were interviewed, and their responses were recorded. Results: A total of 99 patients were included, with a mean age of 46.667 months. Of these, 38 were completely unvaccinated. The geographical penetration and knowledge of the vaccination program were good. Recurrent illness was the most common reason, followed by coronavirus disease of 2019 (COVID-19) and worry about side effects. The reasons were not measles-containing vaccines (MCV)—specific. Two patterns emerged while analyzing responses: antivaccine sentiments or situational issues. Parents’ responses to nonvaccination were independent of their education. Parents who never visited vaccination centers or who did not give vaccines to any child in the family expressed more antivaccine sentiments. Parents who visited the center at least once or who gave the vaccine to at least one child in the family expressed more situational issues. Conclusion: In children suffering from measles, various factors resulted in nonvaccination. Understanding the causes would lead to ways to improve vaccination coverage.